Improving Healthcare Efficiency with Data Analytics : A Case Study on SQL-Based Patient Information Systems - Deepak Chanda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Billions of patient data are generated every day in order to make the most of operational performance and enhance patient care to the health-care organization. This paper investigates the design and implementation of SQL-based Patient Information Systems (PIS) for high efficient data driven healthcare decision making. This research generates a case study where Structured Query Language (SQL) techniques optimize the storage, retrieval, and analytics of such data, resulting in reduced patient wait time and improved resource allocation. SQL-based analytics enables significantly more efficient healthcare workflows because we can see how this helps with data analytics to drive operational efficiency.